Au‐Pd Bimetallic Nanoparticles Immobilised on Titanate Nanotubes: A Highly Active Catalyst for Selective Oxidation. Issue 23 (29th November 2017) - Khawaji, Motaz; Chadwick, David
Abstract: In this work, a highly active Au‐Pd/Ti‐NT catalyst has been produced by using colloidal synthesis and immobilisation on essentially sodium‐free Ti‐nanotubes (NTs). The new catalyst has markedly superior catalytic activity (turnover frequency>19 000 h −1 ) for the selective oxidation of benzyl alcohol compared with similar catalysts reported in the literature, and to Au‐Pd catalysts supported on Ti‐NTs prepared by adsorption, as well as conventional Au‐Pd/TiO2 prepared by impregnation. The superior catalytic activity of the catalyst is shown to be a result of the high metal dispersion on the external surfaces of Ti‐NTs, the narrow particle size distribution and the consistent formation of Au‐Pd mixed alloy nanoparticles in close to a 1:1 weight ratio. In repeated use, the Au‐Pd/Ti‐NT catalyst showed only a modest fall in activity, which is shown by FTIR to be associated mainly with the irreversible adsorption of benzoic acid and benzyl benzoate by the catalyst. Abstract : A highly active Au‐Pd/Ti‐nanotube (NT) catalyst has been produced by using colloidal synthesis and immobilization on essentially sodium‐free titanate nanotubes (Ti‐NT). The new catalyst has markedly superior catalytic activity (turnover frequency>19 000 h −1 ) for the selective oxidation of benzyl alcohol compared with similar catalysts reported in the literature, and to Au‐Pd catalysts supported on Ti‐NTs prepared by adsorption, as well as conventional Au‐Pd/TiO2 prepared by impregnation.